Biokinetics of microbial consortia using biogenic sulfur as a novel electron donor for sustainable denitrification. (December 2018) - Kostrytsia, Anastasiia; Papirio, Stefano; Morrison, Liam; Ijaz, Umer Zeeshan; Collins, Gavin; Lens, Piet N.L.; Esposito, Giovanni
Graphical abstract: Highlights: Biogenic S 0 considerably enhances denitrification and denitritation biokinetics. S 0 had a median particle size of 4.69 µm and a specific surface area of 3.38 m 2 /g. Removals of 223.0 mg NO3 – -N/g VSS·d and 339.5 mg NO2 – -N/g VSS·d were achieved. Biogenic S 0 induced a lower NO2 – -N build-up alleviating the denitrifying activity. Thiobacillus, Moheibacter and Thermomonas were the most abundant genera. Abstract: In this study, the biokinetics of autotrophic denitrification with biogenic S 0 (ADBIOS) for the treatment of nitrogen pollution in wastewaters were investigated. The used biogenic S 0, a by-product of gas desulfurization, was an elemental microcrystalline orthorhombic sulfur with a median size of 4.69 µm and a specific surface area of 3.38 m 2 /g, which made S 0 particularly reactive and bioavailable. During denitritation, the biomass enriched on nitrite (NO2 – ) was capable of degrading up to 240 mg/l NO2 – -N with a denitritation activity of 339.5 mg NO2 – -N/g VSS·d. The use of biogenic S 0 induced a low NO2 – -N accumulation, hindering the NO2 – -N negative impact on the denitrifying consortia and resulting in a specific denitrification activity of 223.0 mg NO3 – -N/g VSS·d. Besides Thiobacillus being the most abundant genus, Moheibacter and Thermomonas were predominantly selected for denitrification and denitritation, respectively.